2021
DOI: 10.1177/15459683211028548
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hemodynamic Responses to the Difficulty Level of Ambulatory Tasks in Patients With Parkinson’s Disease: A Systematic Review and Meta-Analysis

Abstract: Background. Ambulatory tasks are the important components of balance training which effectively improve postural stability and functional activities in persons with Parkinson’s disease (PD). The difficulty level of an ambulatory task is usually set in the form of attention, direction, speed, or amplitude requirement. Objectives. This study aimed to explore the neural mechanisms of cerebral hemodynamic responses to the difficulty level of ambulatory tasks in persons with PD. Methods. We included ten studies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The number of studies or the percent of heterogeneity did not drive the somewhat higher effect size for high-intensity training effects in NEU (N s = 12, I 2 = 71 %) than HOA (N s =14, I 2 = 49 %). While there have been reviews examining the effects of fitness, acute and chronic bouts of exercise on markers of NP in PwMS, PwPD, and PwST, none did metaanalytically examine interactions among exercise type, exercise intensity, NP domains, and populations (Ada et al, 2006;Calautti and Baron, 2003;Cruickshank et al, 2015;Diechmann et al, 2021;Dorsch et al, 2018;Ferreira et al, 2021;Gamborg et al, 2022;Hvid et al, 2021;Jorgensen et al, 2017;Lin et al, 2021;Ploughman et al, 2015;Ramazzina et al, 2017;Roeder et al, 2015;Ruiz-Gonzalez et al, 2021;Salter et al, 2016;Sandroff et al, 2020;Tablerion et al, 2020;Tillman et al, 2015;Wonsetler and Bowden, 2017). Our results in NEU agree with the general conclusions of these reviews that high-intensity AT is a feasible rehabilitation option for each of the three patient groups with the caveat that potential intensity-related side effects rarely assessed or reported (see limitation 4 in Section 4.4).…”
Section: High-intensity Exercise Interacts In Its Effects On Np With ...mentioning
confidence: 99%
“…The number of studies or the percent of heterogeneity did not drive the somewhat higher effect size for high-intensity training effects in NEU (N s = 12, I 2 = 71 %) than HOA (N s =14, I 2 = 49 %). While there have been reviews examining the effects of fitness, acute and chronic bouts of exercise on markers of NP in PwMS, PwPD, and PwST, none did metaanalytically examine interactions among exercise type, exercise intensity, NP domains, and populations (Ada et al, 2006;Calautti and Baron, 2003;Cruickshank et al, 2015;Diechmann et al, 2021;Dorsch et al, 2018;Ferreira et al, 2021;Gamborg et al, 2022;Hvid et al, 2021;Jorgensen et al, 2017;Lin et al, 2021;Ploughman et al, 2015;Ramazzina et al, 2017;Roeder et al, 2015;Ruiz-Gonzalez et al, 2021;Salter et al, 2016;Sandroff et al, 2020;Tablerion et al, 2020;Tillman et al, 2015;Wonsetler and Bowden, 2017). Our results in NEU agree with the general conclusions of these reviews that high-intensity AT is a feasible rehabilitation option for each of the three patient groups with the caveat that potential intensity-related side effects rarely assessed or reported (see limitation 4 in Section 4.4).…”
Section: High-intensity Exercise Interacts In Its Effects On Np With ...mentioning
confidence: 99%
“…If two factors are strongly correlated with each other ( r > 0.7), only the factor with the higher proportion of variance in the single-variable model was entered into the first mixed-variable regression model. A subgroup analysis was used to investigate factors contributing to heterogeneity when the number of studies was insufficient to conduct a meta-regression ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…Compared with EEG, fMRI, and PET, portable fNIRS allows the recording of brain signals during walking tasks in real environments. A meta-analysis of PD based on fNIRS including 10 studies that focused on the oxyhemoglobin in the prefrontal cortex (PFC) of individuals with PD during different difficulty levels of ambulatory walking tasks showed that, compared to healthy older individuals, individuals with PD in the on state showed increased mobilization of the PFC, while during the off-state no significant changes were identified [ 19 ]. In another review, which included 5 fNIRS studies related to PD, the activation of PFC in individuals with PD was higher than that in older adults during the walking task performed at a comfortable pace [ 17 ].…”
Section: Introductionmentioning
confidence: 99%